1981
DOI: 10.1080/03015521.1981.10425426
|View full text |Cite
|
Sign up to set email alerts
|

Pasture irrigation in the Mackenzie Basin

Abstract: Yields of 25 species and cultivars were compared under irrigated and dryland management on a soil of the Grampians set. Species were grown as pure standards at 3 fertiliser levels (0, 250, or 800 kg per ha per a superphosphate for legumes plus 0, 115, or 345 kg per ha per a of nitrogen for grasses) with basal sulphur and molybdenum added for all species. Depending on species, herbage was cut and removed under either a 6-week or 4-week cutting interval for 2 or 3 years. Yields from 5 legume treatments exceeded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

1982
1982
2000
2000

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 10 publications
2
13
0
Order By: Relevance
“…This was larger than had been reported earlier for the same Streamlands soil under trickle and spray lITIgation (Scott & Maunsell 1981). Soils show greater leaching of sulphur than of phosphorus, and we suspect that high rates of fertiliser were needed to counter the leaching of sulphur under borderdyke irrigation.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…This was larger than had been reported earlier for the same Streamlands soil under trickle and spray lITIgation (Scott & Maunsell 1981). Soils show greater leaching of sulphur than of phosphorus, and we suspect that high rates of fertiliser were needed to counter the leaching of sulphur under borderdyke irrigation.…”
Section: Discussionmentioning
confidence: 56%
“…They occur in the zone of low rainfall, which has limited their agricultural development in the past. However, the advent of irrigation makes them potentially the most productive soils in the high country, as demonstrated by yields of pure species stands (Scott & Maunsell 1981). Similarly, the present work with species mixtures has shown that high hay yields can be obtained.…”
Section: Discussionmentioning
confidence: 78%
“…Pasture herbage production in excess of 15 t DM/ha/yr under irrigation and 2 -5 t DM/ha/yr without irrigation was measured on a deep Streamland soil by Scott & Maunsell (1981). At the other extreme irrigation of very shallow, stony Labreck soils yielded only 3.7 -5.7 t DM/ha/yr (Scott et a/ 1982). At Tara Hills High Country Research Station near Omarama, an irrigated shallow, stony Mackenzie soil, typically produces 9.5 t DM/ha/yr from established pasture (Greenwood unpub.…”
Section: Introductionmentioning
confidence: 99%
“…Pasture establishment on the stony soils in the Upper Waitakl Basin is slow and, under irrigation, pastures can remain clover dominant for many years (Scott et al 1982). It Is important that this phase of pasture development be taken into account in the economic planning of irrigation schemes.…”
Section: Introductionmentioning
confidence: 99%
“…Although N fixation rates were not measured, they would be expected to be high (c. 400-600 kg N ha-'yr" 1 ) during the early pasture development stage (Hoglund et al 1979). In a study in the same region on a brown-grey earth soil, the N fixation rate was estimated to be in this range from the difference in pasture growth and N content of legume versus grass swards (Scott & Maunsell 1981).…”
Section: Nitrogen Cyclementioning
confidence: 99%